IMPLEMENTASI METODE FUZZY TSUKAMOTO BERBASIS WEBSITE PADA PENERIMAAN KARYAWAN BARU DI PT JAVA INDOSINERGI CREATIVE - Rohman, Ahmad Zainur; Moh Ahsan; Akhmad Zaini (Fakultas Sains dan Teknologi, 2023)
Challenges that must be overcome to help PT. Java Indosinergi Creative with its employee selection process developed a decision support system. Currently, companies rely on a manual approach, which can produce ineffective results and poor accuracy. Tsukamoto's Fuzzy method is used in Indosinergi Creative's Java decision support system software which assists in the hiring process, enabling faster processing and providing recommendations and considerations for decision making at later stages of the hiring process. By comparing expert ratings with those generated by other ranking algorithms, this study using Fuzzy Tsukamoto provides useful information for making hiring decisions. The authors' questionnaire study found that, on average, respondents scored 79.38% when using this decision aid system.